Implementasi Kebijakan Perekrutan dan Seleksi Bagi Calon Anggota Legislatif Dewan Pengurus Wilayah Partai Kebangkitan Bangsa Provinsi Sulawesi Utara Pada Pemilu 2019 - Djalal, Muid; Pati, Agustinus B.; Mingkid, Elfie (Sam Ratulangi University, 2023)
This research aims to analyze the implementation of recruitment and selection policies for legislative candidates in the Regional Executive Board of the National Awakening Party of North Sulawesi Province in the 2019 elections. This research was conducted in approximately 4 months from January to April 2023. The research was conducted at the DPW PKB Office of North Sulawesi Province located in Lingkungan I, Tikala Ares Village, Tikala District, Manado City. Data collection techniques used in this research are observation and field studies, interviews, literature studies and qualitative, audio and visual documents. This research uses two sources of primary data and secondary data. Primary data is collected from the first source. The primary data sources in this study are informants who have been determined, while secondary data sources are collected as support from the first source. Secondary data sources can also be said to be data arranged in the form of documents consisting of documentation, articles, magazines and others that can support the primary data that has been obtained. Data analysis conducted in this research is by reducing data, presenting data and drawing conclusions or verification. The research on the implementation of recruitment and selection policies for legislative candidates at the DPW PKB of North Sulawesi Province shows that communication aspects, human resource aspects, disposition aspects, and bureaucratic structures in the recruitment and selection of prospective board members from the North Sulawesi PKB have not been carried out optimally in each process carried out.